2012
DOI: 10.1093/infdis/jis531
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Establishing Routine Influenza Sentinel Surveillance in Ethiopia, 2008-2010

Abstract: Ethiopia launched influenza surveillance in November 2008. By October 2010, 176 patients evaluated at 5 sentinel health facilities in Addis Ababa met case definitions for influenza-like illness or severe acute respiratory illness (SARI). Most patients (131 [74%]) were children aged 0-4 years. Twelve patients (7%) were positive for influenza virus. Most patients (109 [93%]) were aged <5 years, of whom only 3 (2.8%) had laboratory-confirmed influenza. Low awareness of influenza by healthcare workers, mispercepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 12 publications
1
24
1
Order By: Relevance
“…3 The more widespread use of the familiar IMCI/IMAI pneumonia guidelines for influenza surveillance in resource‐poor countries—where healthcare personnel are limited, healthcare systems are overburdened, 18 and influenza seasonality is less discrete 2—could allow for the integration of hospital‐based influenza surveillance into broader pneumonia surveillance platforms that may be more sustainable. It could also allow for influenza burden and epidemiology to be described in the context of a more familiar clinical and public health syndrome—pneumonia—that resonates widely with global health policymakers like the Gates Foundation and GAVI,5, 6 dovetails with the UN's Millennium Development Goals 19 and is more easily recognizable to clinicians 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The more widespread use of the familiar IMCI/IMAI pneumonia guidelines for influenza surveillance in resource‐poor countries—where healthcare personnel are limited, healthcare systems are overburdened, 18 and influenza seasonality is less discrete 2—could allow for the integration of hospital‐based influenza surveillance into broader pneumonia surveillance platforms that may be more sustainable. It could also allow for influenza burden and epidemiology to be described in the context of a more familiar clinical and public health syndrome—pneumonia—that resonates widely with global health policymakers like the Gates Foundation and GAVI,5, 6 dovetails with the UN's Millennium Development Goals 19 and is more easily recognizable to clinicians 8…”
Section: Discussionmentioning
confidence: 99%
“…The term SARI does not appear in any of these documents. In addition, lack of familiarity with SARI among clinicians is a major challenge for SARI surveillance8 …”
Section: Introductionmentioning
confidence: 99%
“…To address this gap and generate evidence in Ethiopia, severe acute respiratory infections (SARI) and influenza like illness (ILI) sentinel surveillance was established in November 2008 [16]. The Ethiopian Public Health Institute (EPHI) has adapted and prepared an influenza sentinel surveillance implementation manual [17].…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates the sentinel data in Egypt and Morocco [30], which confirmed that the peak of A(H1N1)pdm09 incidence occurred between November 2009 and January 2010. Similarly, to Djibouti’s neighbour, Ethiopia, which reported its first two cases in June 2009 (first wave), followed by a lapse until early 2010 (second wave), when more cases were noticed [31]. Although this scenario was acceptable to the regional WHO EMR office, it should be considered carefully since countries with functional surveillance systems were likely to detect and report the pandemic circulation earlier than those without these surveillance systems.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore observed that it was difficult to propose an estimate of the actual epidemic impact, because the different patterns reported from neighbouring countries ( e.g. , Ethiopia [31]) indicated that incident cases might have been underreported. We attempted to provide additional epidemiological information through this seroprevalence study of the Djiboutian population, which happened in the winter of 2010 (November 2010 to February 2011).…”
Section: Discussionmentioning
confidence: 99%